Comparative evaluation of treatment of angular bone defect related to over-erupted tooth using guided tissue regeneration (GTR) followed by orthodontic intrusion (OI) versus OI followed by GTR: a controlled clinical trial - Rehab F. Ghouraba; Neveen Fakhry Abotaha; Sara Mohamed Ahmed Sagha (BMC, 2024)
Abstract Background Prematurity resulted from pathological migration of periodontally involved teeth with the loss of vertical stopping points between teeth, which can lead to teeth over eruption with dimensional changes favoring occlusal discrepancies. Therefore, evaluating and comparing the effect of guided tissue regeneration followed by orthodontic intrusion as opposed to orthodontic intrusion tracked by guided tissue regeneration in the treatment of an over-erupted tooth with angular bone loss. Methods Twenty teeth in ten cases were selected with at least two teeth with vertical over-eruption and angular bone loss with the presence of their opposing. In group one, ten teeth over-erupted were treated by guided tissue regeneration followed by orthodontic intrusion, whereas, in group two, ten teeth over-erupted were treated by orthodontic intrusion followed by guided tissue regeneration. They were evaluated clinically for pocket depth, bleeding on probing, and tooth mobility. Radiographical evaluation assessed by cone beam computed tomography. Results Clinically, there existed a statistically significant difference (P value ≤ 0.05) in favor of group one at six months post and in favor of group two at one year from re-evaluation regarding pocket depth and tooth mobility. Radiographically, in group one, there was a statistically significant improvement (P value ≤ 0.05) at six months post-guided tissue regeneration or orthodontic intrusion regarding defect depth and dimensional changes of the defect area, with a statistically significant difference (P value ≤ 0.05) in favor of group two at one year from re-evaluation phase regarding defect depth and defect area dimensional changes. Conclusion There was a short-term improvement in group one, which deteriorated over a long period compared with group two, so it is preferable to start orthodontic intrusion before guided tissue regeneration.